Three Interventions to Reduce Irregular Migration and Promote Alternatives : An Experiment in The Gambia - Bah, Tijan; Batista, Catia; Gubert, Flore; McKenzie, David (World Bank, Washington, DC, 2022)
Irregular migration from Africa to Europe attracts substantial policy attention. Although international migration can enable people from developing countries to dramatically increase their incomes, the absence of legal channels and the chance of higher incomes can induce people to take part in risky journeys that can involve a low chance of success, and the potential for human rights abuses and loss of life. The most common policy responses have been efforts to deter this form of migration through increased enforcement, and through information campaigns that emphasize the dangers associated with irregular migration. However, evidence on the effectiveness of such campaigns is limited, and such policies may not be enough if they do not offer alternative possibilities for improving livelihoods. We designed an experiment in The Gambia to test different approaches.